2020
DOI: 10.1007/s10903-020-01087-2
|View full text |Cite
|
Sign up to set email alerts
|

Self-rated Physical, Mental, Oral, and Cognitive Health in Older Korean Immigrants: The Role of Health Indicators and Sociocultural Factors

Abstract: Objectives: Guided by the models of health assessment and social determinants of health, we examined predictors of self-rated physical, mental, oral, and cognitive health of older Korean immigrants. Methods: Data came from the Study of Older Korean Americans (SOKA; N = 2,061, Mean age = 73.2). Multivariate regression models of self-ratings of health were tested with health indicators (both domain-specific and other health indicators including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
(51 reference statements)
0
3
1
Order By: Relevance
“…Previous research has indicated that low-income Asian Americans exhibit higher levels of psychological distress than higher income Asian Americans (McMillan et al, 2010). Furthermore, past studies exploring psychological distress among Asian Americans but not specifically seeking low-income participants have reported lower levels of psychological distress using the K6 measure compared to the present study (Jang et al, 2018; Jang et al, 2021). Thus, coping with oppression may be particularly difficult for low-income Asian Americans.…”
Section: Discussioncontrasting
confidence: 69%
“…Previous research has indicated that low-income Asian Americans exhibit higher levels of psychological distress than higher income Asian Americans (McMillan et al, 2010). Furthermore, past studies exploring psychological distress among Asian Americans but not specifically seeking low-income participants have reported lower levels of psychological distress using the K6 measure compared to the present study (Jang et al, 2018; Jang et al, 2021). Thus, coping with oppression may be particularly difficult for low-income Asian Americans.…”
Section: Discussioncontrasting
confidence: 69%
“…Further studies will be important to investigate whether the improvement of factors related to SROH contributes to the improvement of SROH or quality of life. Second, factors that might be associated with SROH, such as socioeconomic status [ 14 , 48 ], social capital [ 2 ], psychosocial factors [ 6 , 49 ], and systemic conditions [ 50 , 51 ], were not considered. In addition, according to the Japanese School Health Survey in 2019 [ 52 ], there are differences in the proportion of students aged 5–17 years with decayed teeth among the surveyed regions.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 By following recent studies, we treated self-rated mental health as a continuous variable. 33,[35][36][37] Self-rated life satisfaction was measured based on the following question: "How do you feel about your life as a whole right now?" Responses were coded from "0" (very dissatisfied) to "10" (very satisfied).…”
Section: Methodsmentioning
confidence: 99%
“… 33 , 34 By following recent studies, we treated self-rated mental health as a continuous variable. 33 , 35 - 37 …”
Section: Methodsmentioning
confidence: 99%